Trump and the deeper crisis - Young, Kevin A.; Schwartz, Michael, 1942-; Lachmann, Richard (Political power and social theory, 2022)
While many analysts emphasize Trump's uniqueness, he can also be viewed as a symptom of a deeper systemic crisis. This collection examines the roots, impacts, and future prospects of Trumpism as well as the possibilities for combatting it. Chapters analyze the role of racism and xenophobia, evangelical religion, and elite support in enabling Trump's political ascent, demonstrating how both his demagogic style and his policies draw from the historic repertoire of the Right. The authors also trace the impacts of his presidency on inequality, health, ecological destruction, and U.S. empire. As far-right forces cement their hold on the Republican Party, and as the Democratic Party appears unable to stop them, what lies ahead? The authors argue that confronting Trumpism requires a frontal attack on the conditions that incubated the monster.